Nutrition Justice: Uncovering Invisible Pathways to Malnutrition - Hanieh, Sarah; High, Holly; Boulton, John (Frontiers in Endocrinology, 2020)
We propose the use of the analytic frame of “nutrition justice” to reconcile the separate imperatives of Global Health for nutritional sufficiency for all, the requirement to eradicate childhood malnutrition, and the need for strategies to check the emerging pandemic of the double burden of malnutrition in the Global South. Malnutrition and its consequences of growth stunting are the result of disruption to the nutritional ecology of childhood from structural violence. This is mediated through loss of food security and perturbation to the cultural status of food, and on the prerequisites for nurture during infancy and early childhood. These socio-political factors obscure the role of biological adaptation to nutritional constraint on growth and hence the causal pathway to the double burden of malnutrition. In this paper we describe how the effects of historical and contemporary structural violence on the nutritional ecology of childhood are mediated using the examples of remote Aboriginal Australia and the Lao PDR. Both populations live by force of circumstance in a “metabolic ghetto” that has disrupted the prerequisites for parental nurturing through loss of food security and of traditional sources of transitional staple foods for weaning. Growth faltering and stunting of stature are markers of adaptation to nutritional constraint yet are also the first steps on the track to the double burden. We discuss the implications of these observations for strategies for global food sufficiency by mean of a thought-experiment of the effect of food and nutrient sufficiency for growth on future health and metabolic adaptation.